A pilot study of cerebral metabolism and serotonin 5-HT2A receptor occupancy in rats treated with the psychedelic tryptamine DMT in conjunction with the MAO inhibitor harmine - Egger, Klemens; Gudmundsen, Frederik; Jessen, Naja Støckel; Baun, Christina; Poetzsch, Sandra N.; Shalgunov, Vladimir; Herth, Matthias M.; Quednow, Boris B.; Martin-Soelch, Chantal; Dornbierer, Dario; Scheidegger, Milan; Cumming, Paul; et al. (Frontiers in Pharmacology, 2023)
The psychedelic effects of the traditional Amazonian botanical decoction known as ayahuasca are often attributed to agonism at brain serotonin 5-HT2A receptors by N,N-dimethyltryptamine (DMT). To reduce first pass metabolism of oral DMT, ayahuasca preparations additionally contain reversible monoamine oxidase A (MAO-A) inhibitors, namely β-carboline alkaloids such as harmine. However, there is lacking biochemical evidence to substantiate this pharmacokinetic potentiation of DMT in brain via systemic MAO-A inhibition.We measured the pharmacokinetic profile of harmine and/or DMT in rat brain, and tested for pharmacodynamic effects on brain glucose metabolism and DMT occupancy at brain serotonin 5-HT2A receptors. Methods We first measured brain concentrations of harmine and DMT after treatment with harmine and/or DMT at low sub-cutaneous doses (1 mg/kg each) or harmine plus DMT at moderate doses (3 mg/kg each). In the same groups of rats, we also measured ex vivo the effects of these treatments on the availability of serotonin 5-HT2A receptors in frontal cortex. Finally, we explored effects of DMT and/or harmine (1 mg/kg each) on brain glucose metabolism with [ 18 F]FDG-PET.Results confirmed that co-administration of harmine inhibited the formation of the DMT metabolite indole-3-acetic acid (3-IAA) in brain, while correspondingly increasing the cerebral availability of DMT. However, we were unable to detect any significant occupancy by DMT at 5-HT2A receptors measured ex vivo, despite brain DMT concentrations as high as 11.3 µM. We did not observe significant effects of low dose DMT and/or harmine on cerebral [ 18 F]FDG-PET uptake. Conclusions These preliminary results call for further experiments to establish the dose-dependent effects of harmine/DMT on serotonin receptor occupancy and cerebral metabolism.